(untitled) (Fiep Bulletin - online, 2011)
This systematic review aimed to examine the methodological, physical and psychological training of students / athletes in football, discussing the systematic training process for this phase of life. We performed critical analysis of scientific literature that deals with the assumptions of training for children and adolescents. Football is a sport complex and dynamic, with variability of situations, bringing important contributions to the development of children and adolescents. Training in sports training should be based on respect for the stages of development, worrying not specialize in the physical results, reducing the psychological pressures exerted on these individuals, using methods that foster understanding of the game, from the perception, anticipation and decision decision, found in functional structures. Thus, football should be seen as the continuous interaction of methodological aspects (technical and tactical), physical and psychological so that the absence of these elements may cause problems in the sport of football training.